139 Concerns About Fertility Found to Be Major Cause Of COVID-19 Vaccine Hesitancy in the United States. Issue 1 (1st April 2022) - Diaz, P; Zizzo, J; Balaji, NC; Khodamoradi, K; Ramasamy, R
ABSTRACT: Introduction: As of July 2021, three vaccines have been issued Emergency Use Authorization (EUA) by the U.S. Food and Drug Administration (FDA) to combat SARS-CoV-2 with over 65% of U.S. adults having received at least one vaccine dose. However, up to 35% of the population are hesitant or refuse to get vaccinated. As reproductive toxicity studies were not conducted prior to EUA, adults have expressed concern about potential adverse effects of the vaccines on fertility and reproductive health. Objective: We evaluated the current reasons for COVID-19 vaccine hesitancy among the unvaccinated U.S. population and identified their demographic characteristics. Methods: Amazon Mechanical Turk (MTurk) was used to survey the vaccine hesitancy reasons amongst unvaccinated U.S. adult population between June 30, 2021-July 1, 2021. The project title listed for survey participants during distribution was "Covid-19 Vaccine Hesitancy Survey". The study was reviewed by the Institutional Review Board, and it was deemed an exemption. Users with addresses in the U.S., over the age of 18, and received no doses of any coronavirus vaccine at any time were invited to complete an anonymous 32-question survey with an estimated completion time of less than 10 minutes. The first part of the survey focused on identifying attitudes toward the COVID-19 vaccines while the latter queried demographic information such as age, race/ethnicity, and relationship status. Quantitative data was analyzed using by two-sample Z-test on Microsoft Excel (version 16.44) and MATLAB (version R2021a). Results: A total of 914 unvaccinated adults completed our survey (response rate 91.4%) with 53% of respondents identifying as cis-male and 42% as cis-female. Of the participants, 58% indicated 'COVID-19 vaccine side effects or other potential unknown long-term effects' as their reason for remaining unvaccinated and 39% of them believed that 'COVID-19 vaccines can negatively impact reproductive health and/or fertility'. Among those participants that were concerned that COVID-19 vaccines could impact fertility, 42% (p = 0.010) lived in urban settings, 46% (p > 0.001) were married, and 38% (p = 0.020) of individuals were born outside of the U.S. About 1/2 of the participants stated that more information and research conducted on the COVID-19 vaccines would encourage them to get vaccinated. Conclusions: A large portion of the U.S. population remain fearful of the potential side effects associated with the coronavirus vaccines and more specifically negative impacts to their future reproductive health. These results objectively evidence that fertility concerns are significantly contributing to vaccine hesitancy and may continue to be a barrier for years to come if no interventions are made. With almost half of the participants yearning for more information and research this highlights the need for intense investigation and publicly available data on the effect of coronavirus vaccines on fertility. Disclosure: No